Efforts to Increase Investment Awareness Desa Harapan Baru - Nasib Nasib; Sabaruddin Chaniago; Widy Hastuty HS; Ratih Amelia; Ester Hervina Sihombing (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2021)
This community service activity was carried out on the youth of Harapan Baru Village, Sei Lepan District, Langkat Regency. This activity is in the form of a workshop or training which is carried out with socialization by providing materials or modules on tips for successful investing, especially at a young age in village youth. So it is hoped that the partners have a good understanding of investing even in the village. Then the targets to be achieved through this service activity are (1) partners know what the first step is to invest, especially in rural areas, (2) partners can classify which investments have a high level of failure risk, (3) partners have awareness the importance of investing even though they are still at a young age.